Hukum Vaksin MR: Teori Istihalah dan Istihlak versus Fatwa MUI - Alyasa' Abubakar; Ali Abubakar (Sharia and Law Faculty, 2021)
Measles and rubella are infectious diseases that cause very dangerous diseases throughout the world. Both diseases are incurable; can only be prevented by administering the MR (Measles Rubella) vaccine. However, in Indonesia, the implementation of vaccination for these two diseases did not run smoothly due to the circulation of information that the basic ingredients or the process of making vaccines involved elements of pigs. On that basis, the Indonesian Ulema Council issued Fatwa Number 33 of 2018 concerning the Use of Mr (Measles Rubella) Vaccine Products from SII (Serum Institute Of India) for Immunization which stipulates that